History of cholera in Peru in 1991 - Maguiña Vargas, Ciro (2010)
Cholera is an acute infectious disease, its mere mention scary. Until the nineteenth century, cholera was only in Asia and India, then spread along trade routes by almost 6 causing worldwide pandemics from 1817 to 1923. Later again limited to regions of Southeast Asia. Except for isolated epidemics occurred in 1947 in Egypt. The cholera made its appearance in South America in late January 1991, Chancay - Perú, spreading rapidly to other cities like Chimbote, Piura, Callao, Lima and then to almost every department in the Costa, Sierra y Selva Peru and then to almost every American. Despite economic difficulties, labor, logistics, etc. The 1991 epidemic in Peru was handled properly controlled and lethality was one of the lowest in the world. In 2010, America has emerged cholera in Haiti, so we must be alert. This paper aims to present the economic and health conditions to enter Perú, epidemic, management and lessons learned. Keywords: history, epidemic, Cholera, Peru.